Simulation Of An Automatic Fish Netting Tool With Continuous Servo Motor Drive, Hc-Sr04 Distance Sensor And Button, Using Arduino Mega - Muhammad Akmal Mulyono; Eko Siswanto (University of Science and Computer Technology, 2023)
The current fish harvesting system is still not optimal and requires a lot of human power . In every fish farming place, we can see that the fish netting system still uses manual nets, lots of people, and takes a long time. This affects the turnover / income and profit from the fish empowerment business. Therefore, to increase time efficiency, human energy, turnover and profit, this tool is a solution for every fish empowerment location. Because this tool is designed with an automatic system with a continuous servo motor, HC-SR04 distance sensor, push button, with an Arduino Mega base. button as the input command, the empowerer only needs to input the button (push button) to start harvesting cultivated fish, so that this work becomes more efficient in time, human energy, and influences the increase in turnover and business profits.